2022
DOI: 10.1111/aogs.14462
|View full text |Cite
|
Sign up to set email alerts
|

The application of risk models based on machine learning to predict endometriosis‐associated ovarian cancer in patients with endometriosis

Abstract: Introduction:There is currently no satisfactory model for predicting malignant transformation of endometriosis. The aim of this study was to construct and evaluate a risk model incorporating noninvasive clinical parameters to predict endometriosisassociated ovarian cancer (EAOC) in patients with endometriosis. Material and Methods:We enrolled 6809 patients with endometriosis confirmed by pathology, and randomly allocated them to training (n = 4766) and testing cohorts (n = 2043). The proportion of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Phung et al ( 2022 ) revealed that EAOC patients might have a higher BMI compared to patients with OEM. Chao et al ( 2022 ) discovered that the significance of CA125 and CA19-9 in diagnosing EAOC. Our previous study found that age at diagnosis over 42 years, tumor size over 9.2 cm, and elevated CA19-9 and HE4 levels are risk factors for EAOC (Xu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phung et al ( 2022 ) revealed that EAOC patients might have a higher BMI compared to patients with OEM. Chao et al ( 2022 ) discovered that the significance of CA125 and CA19-9 in diagnosing EAOC. Our previous study found that age at diagnosis over 42 years, tumor size over 9.2 cm, and elevated CA19-9 and HE4 levels are risk factors for EAOC (Xu et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…EAOC exhibited distinct clinical characteristics compared to OEM, highlighting the need for a portable and effective preoperative diagnostic model using machine learning. Chao et al ( 2022 ) constructed a diagnostic model for EAOC using gradient decision trees and demonstrated its favorable performance. However, the drawback of this model was its reliance on a computer, which made it inconvenient and limited its widespread usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the CPH index has been identified as the most reliable predictor for postmenopausal patients with malignant tumors, while the R2 prediction index outperforms other indicators in distinguishing malignant tumors for premenopausal individuals ( 135 ). Machine learning algorithms have been employed for the purpose of constructing risk models with the objective of forecasting the probability of malignant transformation of endometriosis in patients ( 136 ).…”
Section: Prediction and Diagnosis Of Malignant Transformation Risk Fa...mentioning
confidence: 99%
“…Knowledge regarding their reproductive prognosis may empower patients, enabling them to adjust their life projects around their condition and increasing their perception of being taken care of, ultimately improving their satisfaction and their adherence to treatment [22,84,85]. Risk models helping clinicians predict which patients are more likely to encounter a malignant transformation of endometriosis may help identify who requires a timely surgical treatment [86]. Chao and co-workers recently developed a risk model through ML that can predict the risk of endometriosis-associated ovarian cancer with sensitivity and specificity both short of 90%.…”
Section: Role In the Choice Of Medical Treatments And In The Customiz...mentioning
confidence: 99%